Lithium‐Sulfur Batteries: Layered Electrodes Based on 3D Hierarchical Porous Carbon and Conducting Polymers for High‐Performance Lithium‐Sulfur Batteries (Small Methods 5/2019). Issue 5 (2nd May 2019) - Zeng, Shuaibo; Li, Xin; Zhong, Hai; Chen, Shaowei; Mai, Yaohua
Abstract : To enhance cycling performance and increase sulfur loading, in article number1900028, Shaowei Chen, Yaohua Mai, and co‐workers present an effective method using hierarchical porous carbon as a sulfur host, along with conducting polymers, to fabricate layered electrodes for lithium‐sulfur batteries.